Towards developing a communication strategy for water re-use in South Africa - Mamabolo, Mamogobo Rosinah (My University, 2020)
This study aimed to develop a communication strategy for water re-use in Basic Education, which included illustrative learning materials which were suitable for online learning. To attain the intended aim, the study focussed on the subsequent objectives: to review and analyse learners’ and educators’ perceptions and understanding (knowledge) of water re-use; to examine strategies that could be employed to gain learners’ and educators’ understanding and acceptance of water re-use; to develop information or learning materials that would educate and enhance their understanding and informed decision making related to water re-use; and to discuss approaches to communicate water re-use in Basic Education. A qualitative orientation utilising participatory action research was employed as a research design for this study. A sample size of 80 participants, from four primary and four secondary schools in Mankweng Township was selected. 40 learners and 40 educators were selected. Convenience sampling was used to select the participants for this study. Data was collected by means of interviews, focus group discussions, workshops, teaching and participant observation. Thereafter, thematic analysis and NVivo software were employed to analyse data. This study employed Geertz’s notion of culture, Vygotsky’s social constructivism and the behaviour ecological model as theoretical frameworks to guide the research. Geertz’s interpretation of cultures was employed to understand culture and its effects on human behaviour, Vygotsky’s social constructivism was employed to understand the process of effective learning in educational contexts and the behaviour ecological model was employed to understand individuals’ behaviours and the background of the given behaviour. Understanding an individual’s behaviour and experiences towards water re-use assisted in developing water re-use illustrative learning materials. It also assisted with a communication strategy, which integrated Steyn and Puth’s steps, in the formulation of a communication strategy, joint approach model and a step by step content of a communication strategy and action plan model. The study revealed that the majority of individuals have negative perceptions and attitudes towards water re-use, due to a lack of awareness, knowledge and education. The “yuck” factor and health apprehensions were revealed to be major causes of such perceptions and attitudes. Education, campaigns and programmes, traditional and v new media, community meetings, rules, policies and regulation were reported as strategies which might be employed to promote water re-use. The study revealed that individuals’ home language must be made use of in all the water re-use promotional strategies. Communication approaches which promoted a platform for community participation, were revealed as appropriate for development programmes. As a result, participatory and development approaches to communication were considered suitable for communicating water re-use in Basic Education. The study further indicated that posters and storyboards were effective illustrative learning materials which could be employed to educate learners and raise their cognition regarding water re-use as a water conservation method. This would increase acceptability, awareness and practice and reduce negative perceptions, attitudes and concerns. The study indicated that water re-use communication should consider an individuals’ environmental, religious and cultural backgrounds, which would affect water re-use projects. The study also indicated that there was a relationship between an individuals’ perceptions, attitudes, education and culture.
Thesis (M.A. (Communication Studies)) -- University of Limpopo, 2020
Keywords: Water re-use; greywater; water; communication; communication strategy; illustrative learning materials; Communication strategy; Communication; Water reuse